Mass-Volume-Area Properties of Frozen Skipjack Tuna - Pimpen Pornchaloempong; Panmanas Sirisomboon; Navapattra Nunak (My University, 2011)
This study investigates the physical properties of Skipjack tuna (Katsuwonus pelamis), including weight, size, volume, apparent density, surface and projected area, and the correlation between these parameters. An analysis of the physical characteristics of the Skipjack tuna suggests that its shape can be broken down into three main sections: the head, the center, and the tail. The central section of Skipjack tuna can be considered a barrel shape with an elliptical cross section, whereas the head and tail can be considered cones with elliptical bases. Linear regression analyses between fish weight and other geometric properties revealed a significant correlation (R2 = 0.74–0.97) to volume, projected area (side and top view), length, width (measured at the thickest part), and perimeter (measured at the thickest part). The results from this systematic analysis could be used in the design of new processes and equipment for Skipjack tuna processing.
Keywords: Skipjack tuna; Meat and Animal Product Quality